The essential oil from Baccharis trimera (Less.) DC improves gastric ulcer healing in rats through modulation of VEGF and MMP-2 activity - Bueno, Gabriela [UNESP]; Chavez Rico, Stefanni Liliane [UNESP]; Périco, Larissa Lucena; Ohara, Rie [UNESP]; Rodrigues, Vinicius Peixoto [UNESP]; Emílio-Silva, Maycon Tavares [UNESP]; Assunção, Renata [UNESP]; Machado da Rocha, Lucia Regina [UNESP]; Nunes, Domingos Sávio; Besten, Michele Aparecida; Heiden, Gustavo; Lima Camargo, Ana Carolina [UNESP]; et al. (Elsevier, 2021)
Ethnopharmacological relevance: Baccharis trimera (Less.) DC known as “carqueja” in Brazil has been acknowledged as a medicinal plant in folk medicine for the treatment of stomach aches and gastrointestinal disorders. Aim of the study: The present study aimed to evaluate the gastroprotective and healing effects of essential oil from B. trimera (EOBT) against gastric ulcer lesions caused by absolute ethanol and acetic acid, respectively, and to identify the mechanism of action of this essential oil in male Wistar rats. Materials and methods: The plant material used to obtain EOBT was collected in the southern region of Brazil and was analyzed by chromatography-mass spectrometry (GCMS) demonstrate its characteristic chemical composition, with carquejyl acetate as its main component. Different doses of EOBT (50, 100, and 200 mg/kg) were administered orally in male Wistar rats as an acute treatment against absolute ethanol-induced gastric lesions. The gastric healing effect of EOBT (100 mg/kg) was evaluated once a day after 7, 10, and 14 days of treatment. After treatment, the stomachs of rats from all groups were collected to measure the lesion area (mm2), the activity of myeloperoxidase (MPO), and the relative expression of caspases −3, −8, −9, cyclooxygenase-1 (COX-1), cyclooxygenase-2 (COX-2), vascular endothelial growth factor (VEGF), and epidermal growth factor (EGF). The zymography method was used to elucidate the activity of matrix metalloproteinase-2 (MMP-2) and −9 (MMP-9) in the healing action of EOBT. We also analyzed toxicological parameters (body weight evolution and biochemical parameters) that could result after treatment with this essential oil for 14 days. Results: Pretreatment with EOBT (100 and 200 mg/kg) significantly decreased the severity of gastric damage induced by absolute ethanol and decreased MPO activity in gastric tissue. After 10 and 14 days of treatment with EOBT (100 mg/kg) once a day, the lesion area was significantly reduced by 61% and 65.5%, respectively, compared to the negative control group. The gastric healing effect of EOBT was followed by a decrease in the expression of COX-1 compared to that in the negative control group. Notably, treatment with EOBT for 14 days increased the expression of VEGF compared to that using an anti-ulcer drug (lansoprazole). Additionally, analyses of MMP-2 and MMP-9 activities in the gastric mucosa confirmed the accelerated gastric healing effect of EOBT, with a significant decrease in the activity of pro-MMP-2. No sign of toxicity was observed after treatment with EOBT for 14 consecutive days. Conclusion: These findings indicated that EOBT was effective in preventing and accelerating ulcer healing by decreasing MPO activity, increasing VEGF expression, and decreasing MMP-2 activity. These actions collectively contribute to the rapid recovery of gastric mucosa following treatment with EOBT, without any observed toxicity.
Keywords: Baccharis trimera (Less.) DC; Essential oil; Gastric ulcer healing; MMP-2; VEGF